Effect of pre-exercise protein ingestion upon VO2, R and perceived exertion during treadmill running. - Wiles, J (1991)
The study investigated the effect of pre-exercise protein ingestion upon the oxygen consumption (VO2), respiratory exchange ratio (R) and perceived exertion (PE) of athletes during treadmill running at intensities of approximately 60, 80, 90 and 100% of their VO2max. Seventeen female athletes aged between 17 and 22 years participated in the study. Subjects completed six assessment sessions, each being preceded by one of the following dietary regimens: a protein solution ingested 3h before assessment (P3), a protein solution ingested 1 h before assessment (P1) and the ingestion of water 1-3 h before assessment (B). The subjects' VO2, R and PE were measured at all exercise intensities using standardized procedures. The results showed that P1 produced significantly higher values for VO2 (P less than 0.05) at all exercise intensities and was associated with an increased PE (P less than 0.01). The findings could have implications for athletes when considering the composition of their pre-exercise meal, especially if performing in activities which require the participants to exercise close to or at their VO2max.